Improving Purity Propylene Glycol by Modifying Glycerol Hydrogenolysis Process - Azizah, Alfina Rahmatul; Fiya, Aqilah Rizky; Istanto, Hassya Marella; Hapsari, Maylani; Fuzyawan, Naza (Journal of Chemical Engineering Research Progress, 2024)
The chemical industry in Indonesia continues to grow in terms of innovation and technology. One field that has experienced a significant increase is supporting materials, such as propylene glycol. The high demand for propylene glycol in its pure form makes modification of propylene glycol necessary. This modification is done by adjusting the molar ratio of hydrogen to glycerol by 5:1 which involves the process of hydrogenolysis. The physical condition (liquid or gas) of each compound was determined based on the vapor pressure equilibrium data of the pure compound, which was calculated using Hysys software with 2 property packages, namely the NRTL (Non-Random Two-Liquid) model and the uniquac model to determine the actual composition of each component. To obtain a high purity of propylene glycol, the process was modified with the addition of a mixer, recycle, splitter, and two distillation processes. The use of two distillations is used to obtain more optimal results.  In the Aspen HYSYS simulation, the reactor used for this process is a conversion reactor because the conversion reactor is the basis of the fluidized bed reactor. From the method that has been carried out, it is found that this modification is very effective in obtaining high propylene glycol purity. The percentage of propylene glycol in the final product increased from 73.5% to 90%. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).